2020
DOI: 10.5770/cgj.23.398
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Reliability of the Clinical Frailty Scale by Geriatrician and Intensivist in Patients Admitted to the Intensive Care Unit

Abstract: Background The Clinical Frailty Scale (CFS) is a commonly used frailty measure in intensive care unit (ICU) settings. We are inter­ested in the test characteristics, especially interrater reliability, of the CFS in ICU by comparing the scores of intensivists to geriatricians. Methods We conducted a prospective cohort study on a convenience sample of newly admitted patients to an ICU in Edmonton, Canada. An intensivist and a resident in Geriatric Medicine (GM) independently assigned a CFS sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…However, it is likely that this bias was limited as there are several studies indicating sufficient interrater reliability of the CFS. [29][30][31][32] Although there is still some variability in interrater agreement, the CFS is prognostically relevant. 30 The present study showed an important direction for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is likely that this bias was limited as there are several studies indicating sufficient interrater reliability of the CFS. [29][30][31][32] Although there is still some variability in interrater agreement, the CFS is prognostically relevant. 30 The present study showed an important direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] Although there is still some variability in interrater agreement, the CFS is prognostically relevant. 30 The present study showed an important direction for future research. The mixed results with respect to the association between CFS score and admission to intensive care shows that more research is needed to understand the dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, outside geriatrics and frailty services, few clinicians receive formal frailty identification training; many lack confidence in this, and desire more frailty education [ 11 ]. When used against a background of care rationing more than for the development of a traditional care plan, the results might not always reflect expert geriatrician judgement [ 12 ]. CFS inter-rater reliability is generally very good [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the CFS, the original publication [ 6 ] established construct validity by comparing it with the frailty index [ 8 ]. Inter-rater reliability of the CFS has been tested in a limited number of patients in three studies [ 9 11 ] and the feasibility was clinically demonstrated in the VIP1 study where CFS was collected in 99.8% of the 5187 patients included [ 1 ]. As a pre-defined sub-study nested within the VIP2 study [ 12 ] we additionally planned to perform a large international assessment of CFS reliability.…”
Section: Introductionmentioning
confidence: 99%